Breast hydatid cyst mimicking fibroadenoma and malignancy: A case report - Karatas, Turgay; Kanlioz, Murat; Akin, Mustafa (Turkish Surgical Assoc, 2013)
Echinococcus granulosis is known as the cause of hydatid cyst disease. It is often seen in many regions of the world, and can cause serious health problems. This parasite can invade tissues in all parts of the body and produce hydatid cysts, although it has been mainly observed in the liver and the lungs. Breast hydatid cysts are encountered rarely. After physical examination, radiological and serological tests are performed on patients with breast hydatid disease. These examinations are helpful for an early diagnosis, but they are insufficient to make a definitive diagnosis, which can only be made according to the results of histopathological examinations. We had a primary diagnosis of either fibroadenoma or malignancy in the breast during the preoperative period of the present case. A precise diagnosis could only be made by histopathological examinations in the postoperative period.
Keywords: Hydatid cyst; breast masses; breast hydatid cyst